Respuesta :

Answer:

The answer to your question is:

 x₁ = 0

x₂ = -3

x₃ = 3

Step-by-step explanation:

Equation   4x³ = 36 x

Process

                   4x³ - 36x = 0

                  4x (x² - 9) = 0

                   4x (x + 3)(x - 3) = 0

      Finally

                4x = 0        x + 3 = 0           x -3 = 0

                x = 0/4        x₂ = -3               x₃ = 3

                x₁ = 0

Answer:

[tex]x=0\text{ or }x=-3\text{ or }x=3[/tex]

Step-by-step explanation:

We have been an equation [tex]4x^3=36x[/tex]. We are asked to find the solutions for our given equation.

First of all, we will subtract [tex]36x[/tex] from both sides as:

[tex]4x^3-36x=36x-36x[/tex]

[tex]4x^3-36x=0[/tex]

Let us factor the given equation.

[tex]4x(x^2-9)=0[/tex]

Use difference of squares:

[tex]4x(x^2-3^2)=0[/tex]

[tex]4x(x+3)(x-3)=0[/tex]

Using zero product property, we will get:

[tex]4x=0\text{ or }(x+3)=0\text{ or }(x-3)=0[/tex]

[tex]x=0\text{ or }x=-3\text{ or }x=3[/tex]

Therefore, the solutions for our given equation would be [tex]x=0\text{ or }x=-3\text{ or }x=3[/tex].